Autoimmune statin-induced myopathy: a case report - Jonathan B. Young; Ibrahim I. Ghobrial (Greater Baltimore Medical Center, 2015)
A 58-year-old woman with a history of statin use presented with a 4-month history of progressive weakness of both shoulders and thighs. Laboratory and electromyography testing confirmed the presence of generalized proximal myopathy and ruled out connective tissue disease, malignancy, or active viral infection. Muscle biopsy was consistent with necrotizing autoimmune myopathy.